El bienestar laboral del talento humano en la empresa Cubiko Obras y Consultoría SAS. (2021)
The objective of this degree project is to identify the level of labor well-being found in the company CUBIKO OBRAS Y CONSULTORIAS SAS, thus determining the main situations that may be affecting the company, conducting an intervention through a survey seeking the participation of all employees. employees, which can identify the problems that are handled there and thus provide support and recommendations to improve their work activities and possible returns.